Supply Chain Management Practices in Services Industry: An Empirical Investigation on Some Selected Services Sector of Bangladesh - Chowdhury, AHM Yeaseen; Alam, Md. Zahedul; Habib, Md. Mamun (International Journal of Supply Chain Management, 2017)
The aim of this study is to examine the supply chain management practices in services industry of Bangladesh. Study revealed that there are differences in practices between manufacturing and services industry with few counts like inventory management, logistics management and use of technology etc. Within the selected sub-sectors, there are differences in the level of practices in supply chain management with banking sector is the highest whereas in hotel industry the practice is the lowest. This study also investigates the effect of supply chain responsiveness in terms of operation system responsiveness, logistic process responsiveness, supplier network responsiveness and competitive advantage of the firm. On the basis of findings, strategic supply chain management practices should be implemented in more detailed ways in services industry of Bangladesh.